Serum thymosin alpha 1 levels in normal and pathological conditions. (31st May 2018) - Pica, Francesca; Gaziano, Roberta; Casalinuovo, Ida Antonia; Moroni, Gabriella; Buè, Cristina; Limongi, Dolores; D'Agostini, Cartesio; Tomino, Carlo; Perricone, Roberto; Palamara, Anna Teresa; Sinibaldi Vallebona, Paola; Garaci, Enrico
ABSTRACT: Introduction : Thymosin alpha 1 (Ta1) is a natural occurring peptide hormone that is crucial for the maintenance of the organism homeostasis. It has been chemically synthesized and used in diseases where the immune system is hindered or malfunctioning. Areas covered : Many clinical trials investigate the Ta1 effects in patients with cancer, infectious diseases and as a vaccine enhancer. The number of diseases that could benefit from Ta1 treatment is increasing. To date, questions remain about the physiological basal levels of Ta1 and the most effective dose and schedule of treatment. Evidence is growing that diseases characterized by deregulation of immune and/or inflammatory responses are associated with serum levels of Ta1 significantly lower than those of healthy individuals: to date, B hepatitis, psoriatic arthritis, multiple sclerosis and sepsis. The sputum of cystic fibrosis patients contains lower levels of Ta1 than healthy controls. These data are consistent with the role of Ta1 as a regulator of immunity, tolerance and inflammation. Expert opinion : Low serum Ta1 levels are predictive and/or associated with different pathological conditions. In case of Ta1 treatment, it is crucial to know the patient's baseline serum Ta1 level to establish effective treatment protocols and monitor their effectiveness over time.